Field assessment of bacteria and nutrient removal by vegetative filter strips - Douglas-Mankin, Kyle R; Okoren, Cairo G (International Journal of Agricultural and Biological Engineering, 2011)
Abstract: Strategies are sought to reduce the impact of nonpoint sources of pollution, including fecal bacteria, and meet TMDL criteria. Vegetative filter strips (VFSs) are one such strategy, though <span style="line-height: 135%; font-family: